Jak badać akwizycję języka obcego w klasie, czyli o zadaniu w perspektywie badań ilościowych i jakościowych - Piotrowski, Sebastian (Neofilolog, 2019)
In studies on second language acquisition in formal settings, techniques characteristic of both qualitative and quantitative research paradigms are applied. In the first part of the article, we present general reflection on the methodology of studies on second language acquisition, with a particular emphasis on the role of exploratory research in the analysis of the process of second language teaching/learning in formal settings. In the second part, we present the concept of task, stressing its usefulness as a basic unit of analysis of the corpus of linguistic data obtained in the classroom.